Multilingualism in the Czech Literature: the classification - Malý, Radek (Bohemica Olomucensia, 2017)
After 1989, in czech literature there are more and more writers, which change the language of their books. But it is not a new phenomenon: also in old czech literature we can find many forms of multilingualism (Latin or German for example). The paper focuses on the issues of multilingualism in czech literature. It tries to classificate it, based on national affiliation of writers, their literary language and other criterions. There is also a possible definition of multilingualism, adapteted for czech literature. It follows presentation of the most important czech authors of books written in other language than czech after 1989 like Libuše Moníková or Michael Stavarič (german), Milan Kundera and Petr Král (french) or Mark Slouka and Jan Novák (english).
Keywords: multilingualism; Czech literature; exil literature